DEVELOPMENT OF A COMPUTER MODULE FOR FORECASTING AND ESTIMATING EFFICIENCY OF BASIC THERAPY OF MULTIPLE SCLEROSIS - F. A. Khabirov; D. Kh. Shakirova; O. A. Dun; T. I. Khaibullin (Фармакоэкономика, 2015)
in the present research is shown that using information and computer technologies can automate the pharmacoeconomic evaluation of the rationality of the appointment and a forecast of efficiency of basic therapy of multiple sclerosis. Criteria of efficiency of immunomodulatory therapy of the multiple sclerosis, taking into account the individual characteristics of each patient, are selected.